Navigating the impact of COVID‐19: Anxiety in the learning environment - Heuver, Tanya; McKendrick-Calder, Lisa; Pollard, Cheryl; Shumka, Christine; Chase, Thomas; Morey, Kylie; Solanki, Shivani (My University, 2021)
A high percentage of post‐secondary students experience anxiety. Anxiety can range from being a helpful stimulus, to completely debilitating. This project explores the relationship between the learning environment and student anxiety.
Keywords: post secondary education; students; anxiety